Interfacial microstructure evolution and mechanical properties of B4C-based composite joints bonded with Ti foil. Issue 15 (15th October 2018) - Li, H.X.; Zhong, Z.H.; Yang, A.K.; Wang, Z.Q.; Wen, Q.; Chen, C.; Song, K.J.; Wu, Y.C.
Abstract: The interfacial microstructure and mechanical properties of B4 C-SiC-TiB2 composite joints diffusion bonded with Ti foil interlayer were investigated. The joints were diffusion bonded in the temperature range of 800–1200 °C with 50 MPa by spark plasma sintering. The results revealed that robust joint could be successfully obtained due to the interface reaction. B4 C reacted with Ti to form nanocrystalline TiB2 and TiC at the interface at 800–1000 °C. Both the reactions between SiC and Ti and between TiB2 and Ti were not observed during joining. A full ceramic joint consisted of micron- and submicron-sized TiB2 and TiC, accompanied with the formation of micro-crack, was achieved for the joint bonded at 1200 °C. Joint strength was evaluated and the maximum shear strength (145 ± 14.1 MPa) was obtained for the joint bonded at 900 °C. Vickers hardness of interlayer increased with increasing the joining temperature.